2018
DOI: 10.1177/1715163518804276
|View full text |Cite
|
Sign up to set email alerts
|

Health care providers’ roles and responsibilities in management of polypharmacy: Results of a modified Delphi

Abstract: Background: Little is known about the roles that allow interprofessional teams to effectively manage older patients experiencing polypharmacy. Objectives: to identify and examine the consensus on salient interprofessional roles, responsibilities and competencies required in managing polypharmacy. Methods: Four focus groups with 35 team members practising in geriatrics were generated to inform survey development. the sessions generated 63 competencies, roles or responsibilities, which were categorized into 4 do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…The participants in our study considered all groups of HCPs to play a crucial role in the deprescribing process. In a recent study, the authors explored different groups of HCPs' perceptions of responsibilities and roles in management of polypharmacy, including FPs, geriatricians, pharmacists, nurses, and social workers (Farrell, Thompson, et al, 2018). Consistent with our results, all groups considered themselves to hold competencies in terms of managing polypharmacy, although the number of identified competencies varied between the groups.…”
Section: Comparison To Existing Literaturesupporting
confidence: 73%
“…The participants in our study considered all groups of HCPs to play a crucial role in the deprescribing process. In a recent study, the authors explored different groups of HCPs' perceptions of responsibilities and roles in management of polypharmacy, including FPs, geriatricians, pharmacists, nurses, and social workers (Farrell, Thompson, et al, 2018). Consistent with our results, all groups considered themselves to hold competencies in terms of managing polypharmacy, although the number of identified competencies varied between the groups.…”
Section: Comparison To Existing Literaturesupporting
confidence: 73%
“…Pharmacists are not the only healthcare professionals who play a critical role in polypharmacy. In a survey of multifaceted healthcare providers, the findings showed that physicians, pharmacists, and nurses all agreed that preventing polypharmacy was a role they all were responsible for [ 23 ]. For example, nursing-led interventions have shown an improved adherence rate to oral (85% to 90%) and inhaled treatment (37 to 71%) in COPD patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of multifaceted healthcare providers, the findings showed that physicians, pharmacists, and nurses all agreed that preventing polypharmacy was a role they all were responsible for [ 23 ]. For example, nursing-led interventions have shown an improved adherence rate to oral (85% to 90%) and inhaled treatment (37 to 71%) in COPD patients [ 23 ]. There are multiple screening tools for physicians to be more mindful of the possibility of adverse effects to PIMs [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…6,8,9 Addressing polypharmacy helps to reduce the chances of inpatient falls, inpatient falls with injuries, increased mortality rates, and increased patient costs. [4][5][6]10,11 However, addressing polypharmacy by deprescribing medications must be done with attention to withdrawal side effects and factors like frailty, which exacerbate the effects of FRIDs. 5,11 The experience of an inpatient fall causes feelings of stress, anxiety, and loss of confidence in patients after the occurrence.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…[5][6][7][8][9]11,17 Researchers cite polypharmacy as hindering the quality of life, increasing the chance of falls with injuries, increasing patient costs, and increasing mortality rates. [4][5][6]10,11 Studies show barriers to deprescribing include FRIDs the patient may be taking, their willingness to cooperate, their patient history, factors related to frailty, and the need for expertise in deprescribing medications due to possible adverse effects. 5,11…”
Section: Reducing Polypharmacymentioning
confidence: 99%